Impact of enteropathogens on faltering growth in a resource-limited setting - Kabir, Furqan; Iqbal, Junaid; Jamil, Zehra; Iqbal, Najeeha Talat; Mallawaarachchi, Indika; Aziz, Fatima; Kalam, Adil; Muneer, Sahrish; Hotwani, Aneeta; Ahmed, Sheraz; Umrani, Fayaz; Syed, Sana; et al. (Frontiers in Nutrition, 2023)
Environmental enteropathy is an important contributor to childhood malnutrition in the developing world. Chronic exposure to fecal pathogens leads to alteration in intestinal structure and function, resulting in impaired gut immune function, malabsorption, and growth faltering leading to environmental enteropathy. Methods: A community-based intervention study was carried out on children till 24 months of age in Matiari district, Pakistan. Blood and fecal specimens were collected from the enrolled children aged 3-6 and 9 months. A real-time PCR-based TaqMan array card (TAC) was used to detect enteropathogens. Results: Giardia, Campylobacter spp., enteroaggregative Escherichia coli (EAEC), Enteropathogenic Escherichia coli (EPEC), Enterotoxigenic Escherichia coli (ETEC), and Cryptosporidium spp. were the most prevailing enteropathogens in terms of overall positivity at both time points. Detection of protozoa at enrollment and nine months was negatively correlated with rate of change in height-for-age Z (ΔHAZ) scores during the first and second years of life. A positive association was found between Giardia, fecal lipocalin (LCN), and alpha 1-Acid Glycoprotein (AGP), while Campylobacter spp. showed positive associations with neopterin (NEO) and myeloperoxidase (MPO). Conclusion: Protozoal colonization is associated with a decline in linear growth velocity during the first two years of life in children living in Environmental enteric dysfunction (EED) endemic settings. Mechanistic studies exploring the role of cumulative microbial colonization, their adaptations to undernutrition, and their influence on gut homeostasis are required to understand symptomatic enteropathogen-induced growth faltering.